CoMFA and CoMSIA Investigations Revealing Novel Insights into the Binding Modes of Dopamine D3 Receptor Agonists - Hübner, Harald; Gmeiner, Peter; Utz, Wolfgang; et al. (Journal of Medicinal Chemistry, 2005)
As an extension of a series of dopamine D3 receptor agonists involving FAUC 54, ex-chiral pool synthesis, and biological evaluation of 3-substituted 7-aminotetrahydroindolizines was performed. Considering the structural features of both series of enantiomers, we developed a novel alignment hypothesis for D3 agonists, allowing for the placement of the aromatic moieties on two alternative, adjacent positions. CoMFA and CoMSIA analyses yielded significant cross-validated q2 values of 0.726 and 0.590, respectively, when a newly invented program application (IRAS) controlling the alignment selection proved to be useful. Employing the CoMFA/CoMSIA contribution maps, we were able to transform a previously constructed homology model of the D3 receptor from an inactive into an activate state. Besides the established ionic interactions, we propose π-stacking with Phe6.51 and a hydrogen bond between His6.55 and the acyl moiety to be primarily involved in the D3 receptor binding of FAUC 54 and its analogues. © 2005 American Chemical Society.
UnivIS-Import:2015-03-09:Pub.2005.nat.dchph.lphch.comfaa